Interacciones medicamentosas potenciales en pacientes geriátricos con polifarmacia de un servicio de Medicina Interna en un Hospital de Alta Complejidad, noviembre - diciembre 2016 - Chirinos Rodriguez, Jessica Marisol (2019)
The objective of this report was to identify the characteristics of potential drug interactions in geriatric patients with polypharmacy from an Internal Medicine service in a Hospital of High Complexity, November - December, 2016. The data was obtained from the review of the therapeutic sheets of 47 patients who met the inclusion criteria; the potential drug interactions were evaluated in the Medscape software, according to the level of significance; in which data analysis was found: the predominant sex was women and the age group of 70-79 years (40,4%). The frequency of potential drug interactions was 47% of 22 patients who had at least one potential interaction and directly proportional to the number of prescriptions, with the average number of prescriptions being 7 to 9 (45%) per patient, which It tells us that as drug consumption increases, the risk of interaction and adverse reactions also increases. According to the Chemical Therapeutic Anatomical Classification (ATC), the most used drugs are those that act at the level of the Digestive System and Metabolism (group A) with 26% (n=30); followed by those that act at the level of the Cardiovascular Apparatus (group C) with 22% (n=25). The frequency of potential interactions with greater significance was 22% (n= 15), mainly pharmacodynamic type, being the potential drugs: levothyroxine-warfarin, with 33% and warfarin-enoxaparin with 20% producing a synergism between them and the frequency of potential interaction of minor significance was 72% (n=54) presenting mostly pharmacokinetic type, being the potential drugs: omeprazole-losartan with 15%, producing potentiation in the effects of ARA II, followed by phenytoin-omeprazole with 13 %, producing an increase in the action of the antiepileptic drug Keyword: Drug interaction, polypharmacy, geriatrics